(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to provide an updated assessment of the importance of humanization in health care in times of a pandemic. Methodology: This study is part of an integrative review of the operationalized literature, based on the following phases: recognition of the theme and distinction of the research question; organization of exclusion and inclusion criteria; consolidation of the chosen studies; distribution of elected works; observation of the research and clarification of the results; finally, the vision of the review understood. Results: Thus, the studies were published in the years 2021 and 2020, being the equivalent of 50% in the year 2021 and about 50% in the year 2020. Therefore, most of the works were from Spain 37.5% and from the Brazil 37.5%, against 12.5% ​​in Argentina and 12.5% ​​in Italy. Conclusion: In view of the above, it was observed that the constant search for the humanization of care is of paramount importance for the improvement of the patient’s condition, as it touches their emotional and even the professionals involved, giving them comfort. For future research, a reflection on the dehumanizing aspect of dying alone is recommended. There are few studies, so knowledge is needed if circumstances similar to everything that occurred during the peak of Covid-19 in 2020 are repeated.